Efficacy of Virtual Reality for Studying People's Pre-evacuation Behavior under Fire. Issue 142 (October 2020) - Bourhim, EL Mostafa; Cherkaoui, Abdelghani
Highlights: Advances in VR technology present new opportunities for fire evacuation research. Technical details about how such virtual environments can be modeled are given. The efficacy of VR simulation for studying human behavior in fire situations is provided. A guiding framework for evaluating the VR simulation is developed Subjective feedback indicated that the VR fire simulation was realistic and engaging. Abstract: The recent proliferation of consumer-level virtual reality (VR) headsets such as the HTC Vive, is creating a growing user-base in demand of highly-controlled immersive virtual environments (VEs). The authors take advantage of the commercial availability of these VR devices to build a high-rise residential buildings fire escape, which provides a highly immersive VR simulation game approach, designed to simulate pre-evacuation human reactions in fire emergencies. We replicated this fire scene in our VE using the unity3D game engine and the HTC Vive head-mounted VR display. The results gathered from this virtual simulation were compared to the data from real fire condition to test the efficacy of the information provided from this VE. Furthermore, we propose a comprehensive evaluation system for VE usability using the analytic hierarchy process (AHP) and the fuzzy evaluation approach. Subjective responses show that our simulation-based VR was effective, realistic, and engaging. Overall, the study results confirm the efficacy of VR technology for research on people's pre-evacuation behavior under fire.